Clinical and Bacterial Risk Factors for Development of Post-Prostate Biopsy Infections - Hasanzadeh, Amir; Black, Peter; Pourmand, Mohammad Reza; Pourmand, Gholamreza (Urology Journal, 2019)
Purpose: To research on clinical and bacterial risk factors and their relationship with post-prostate biopsy infection (PBI). Materials and Methods: In this prospective cohort study, rectal swabs were collected from 158 men prior to prostate biopsy and cultured selectively for identify ciprofloxacin-resistant (FQ-R) gram-negative bacteria. The patient characteristics, phylogenetic background, sequence typing and pulsed field gel electrophoresis (PFGE) pattern were compared in two groups of FQ-R E. coli rectal and clinical isolates. Results: In total, PBI was observed in 20 (12.5%) cases; the most of these subjects were FQ-R-colonized. (17/73 [24%] vs 3/85 [3.5%]; P < 0.001). FQ-R colonization, diabetes, hospitalization and UTI were independent risk factors (95% CI: 1.1-20.1, OR = 4.73; 95% CI: 1.7-25.3, OR = 6.57; 95% CI: 1.9-27.5, OR = 7.22; and 95% CI: 1.2-14.3, OR = 4.05; respectively), that increased the rate of PBI (All P < 0.05). Despite the increase in infections among patients colonized with strains of E. coli ST131, its prevalence was near significance between colonized and infected groups (P = 0.07). The PFGE patterns and antimicrobial susceptibility profiles of rectal and clinical isolates in 13 patients were similar which is remarkably important and informative. Conclusions: The most PBIs originate from FQ-R E. coli rectal colonization. Rectal culture screening and assessment of clinical risk factors can predict the incidence of PBI in patients.